Integrasi Pendekatan Masalah Sosial dan Aset Komunitas Dalam Memberdayakan Masyarakat Desa di Era 4.0 - Wahanani Mawasti; Reva Rizki Amalia (Mahesa Research Center, 2022)
This study describes the stages of empowerment carried out by the Marketer Village Community (Komerce) in empowering rural communities in Purbalingga. The empowerment of the Marketer Village is based on technological developments in the 4.0 era. The research method used is qualitatively descriptive by using purposive interviews, documentation and online data searches. This study concludes that the stages of empowerment carried out by Kampung Marketer integrate social problem mapping and asset based community development (ABCD) approaches. In carrying out the empowerment stages, the role of the empowering subject is dominant in the process of mapping social problems, exploring community assets to planning actions. However, at other stages, empowerment is carried out by involving the participation of village communities as organizers and implementers of empowerment programs in the village in a sustainable manner. In addition, the success of the empowerment carried out is also due to efforts to build positive collaboration with parties outside the village, such as city businessmen as partners. With systematic stages, based on social problems and the potential assets of the village community, Kampung Marketer succeeded in increasing the capacity of the village community, including: knowledge, mindset, skills, a positive climate in the village, as well as increasing economic welfare and community independence.